PERBANDINGAN HEAD OF BED 15° DAN 30° PADA NYERI PUNGGUNG PASIEN POST PERCUTANEOUS CORONARY INTERVENTION (PCI) DI RUANG ICCU RUMAH SAKIT PANTI RAPIH YOGYAKARTA - Elisabeth Caesaradina Dwi Raga Putri; Arimbi Karunia Estri; Herlin Lidya (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2025)
Background: Post-Percutaneous Coronary Intervention (PCI) patients often experience back pain due to bed rest to prevent post-catheterization complications. This pain can reduce comfort, delay recovery, and increase hospital stay. Modifying patient positioning, such as adjusting the Head of Bed (HOB), can be a non-pharmacological measure to reduce back pain. Objective: To determine the difference in effectiveness of the 15° and 30° HOB positions on back pain levels in post-PCI patients in the Intensive Care Unit (ICCU) Panti Rapih Hospital. Methods: This study employed a quasi-experimental design with two independent groups. The study population included all post-PCI patients with radial access hospitalized in the ICCU. A total of 40 respondents were selected using simple random sampling according to the inclusion criteria and then divided into two groups, each with 20 participants in the 15° HOB and the 30° HOB. The research instruments used included an inclinometer to determine the degree of bed incline, a Visual Analog Scale (VAS) to assess pain levels before and after the intervention, and an observation sheet for data recording. Results: Analysis using the Wilcoxon test showed that both the 15° and 30° head of bed (HB) groups experienced significant reductions in back pain (p < 0.001). However, the Mann-Whitney test showed no significant difference between the two groups in the level of pain reduction (p > 0.05). This indicates that both positions are equally effective in reducing back pain in post-PCI patients. Implications: Both the 15° and 30° head of bed (HB) positions can be used as non-pharmacological measures to reduce back pain in post-PCI patients. The nurse can adjust the position based on comfort and the clinical condition of each patient. Keywords: Head of Bed 15°; Head of Bed 30°; Back pain